Informationswege von Lehrern – eine empirische Untersuchung zum Thema „Land- und Ernährungswirtschaft“ - Flath, Martina; Schockemöhle, Johanna (Journal of Geography Education, 2004)
The present paper introduces the results of a study by order of the German Federal Ministry of Consumer Protection, Food and Agriculture. The study had the objective to identify information paths of teachers in order to evaluate the potential of targeted publications. It is demonstrated that teachers of different levels of general education differ in part significantly in their search for teaching material and information literature on agriculture and food. Primary school teachers, for instance, attach more importance to farmers and agricultural or food manufacturers’ associations as valuable resources than teachers of secondary schools do. On the one hand, these results indicate that primary school teachers take a relatively active part in discovery on family-farms. On the other hand, these results suggest that the different associations keep ready appropriate information literature especially for teachers of primary schools. These allegations are corroborated by an unexpectedly high proportion of primary school teachers who use that kind of factual information to a great extend; but they are invalidated by a relatively evenly distributed degree of utilisation among all groups of teachers. Some factors tend to influence the importance of resources for information about agriculture or food positively: private contacts, the offer of didactically and methodologically adapted and cost-saving material as well as easy local accessibility or easy availability due to simple communication channels. Regarding different types of media, the study indicates that teachers concentrate not only on one particular type of media when looking for information. Their behaviour is characterised by a balanced use of different kinds of media. However, the intensive use of schoolbooks among all groups of teachers is noticeable as well as the little importance of agrarian literature as a source of information.